2011
DOI: 10.1002/jsfa.4413
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of nitrogen fertilizer use and N-saving potential for improvement of food production and nitrogen use efficiency in China

Abstract: The study suggests that to achieve the goals of regional yield improvement, it is necessary to readjust and optimize regional distribution of N fertilizer use between the N-poor and N-rich regions in China, in combination with other nutrient management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…However, several long-term field studies have observed a reduced yield response to continuously increasing chemical fertilizer use . Previous analysis showed that the growth rate of grain yields was closely related to the increase in fertilizer use during 1980-1985, while there was a declining trend of yield response to the increase in fertilizer use over the subsequent time period , and an increasing number of regions with little or no yield response to changes in fertilizer rate over time after the 1990s (Wang et al 2011). As our results indicated, regional yield responses to fertilizer added were positive (Table 1) over time, while they were higher for Northeast China and East China, as compared to North China and Central and Southwest China, with regression model coefficients (in kg kg −1 ) of 9.3, 5.7, 1.7, and 1.2, respectively, for Northeast China, East China, North China, and Central and Southwest China.…”
Section: Regional Grain Yields In Responses To Fertilizer Use and Annmentioning
confidence: 99%
See 4 more Smart Citations
“…However, several long-term field studies have observed a reduced yield response to continuously increasing chemical fertilizer use . Previous analysis showed that the growth rate of grain yields was closely related to the increase in fertilizer use during 1980-1985, while there was a declining trend of yield response to the increase in fertilizer use over the subsequent time period , and an increasing number of regions with little or no yield response to changes in fertilizer rate over time after the 1990s (Wang et al 2011). As our results indicated, regional yield responses to fertilizer added were positive (Table 1) over time, while they were higher for Northeast China and East China, as compared to North China and Central and Southwest China, with regression model coefficients (in kg kg −1 ) of 9.3, 5.7, 1.7, and 1.2, respectively, for Northeast China, East China, North China, and Central and Southwest China.…”
Section: Regional Grain Yields In Responses To Fertilizer Use and Annmentioning
confidence: 99%
“…Over the last 20 years, fertilizer use in China has rapidly increased to meet the increasing food demand of its growing population. Fertilizer use plays an irreplaceable role in China's food production, resulting in a 50 % increase in the total grain production in China (Wang et al 2011). However, several long-term field studies have observed a reduced yield response to continuously increasing chemical fertilizer use .…”
Section: Regional Grain Yields In Responses To Fertilizer Use and Annmentioning
confidence: 99%
See 3 more Smart Citations